Antimicrobials use pattern under organized and unorganized dairy production conditions in southern India - RAOSAHEB, CHITALKAR VASANT; MANIMARAN, AYYASAMY; SIVARAM, MUNIANDY; JEYAKUMAR, SAKTHIVEL (The Indian Journal of Animal Sciences, 2020)
The aim of this study was to estimate the antimicrobial use pattern against various clinical conditions under organized and unorganized dairy production conditions in selected areas of Tamil Nadu and Karnataka. Four organized dairy farms and one veterinary teaching hospital were surveyed covering Krishnagiri and Kolar districts of Tamil Nadu and Karnataka (India), respectively. The data were collected from practicing veterinarians (104) through questionnaires and in farms through treatment records. Milk samples (100) were also qualitatively screened for antibiotic residues in these farms. Mastitis and other udder health related problems were the most common (34%) followed by gastro intestinal tract (GIT) (20%) and postpartum uterine infections (PUI: 20%) in organized dairy farms. Overall, penicillins and its combinations (40%) and tetracyclines (33%) group of antibiotics were mostly used for treatment of above clinical conditions. About 13% of the milk samples were qualitatively positive for antibiotic residues in organized farms. Veterinarians rated mastitis (22%) followed by PUI (15%), respiratory disorders (14%) and GIT problems (12%) as the most common reasons for administrating antibiotics in field conditions, based on Garrett’s ranking method. Penicillins, cephalosporins and tetracycline (36%) group of antibiotics were the most commonly prescribed for all clinical conditions. In the case of clinical mastitis, 20% veterinarians preferred cephalosporins group followed by penicillins and its combination (18%). It is concluded that mastitis is the most common reason for antibiotic usage in dairy animals and thus, an effective mastitis management programs are required to reduce the antimicrobial consumption.